Root Morphology of First Permanent Molars Extracted from Adult Dental Patients of Similar Ethnicity in Dar-Es-Salaam, Tanzania - Lorna Celia Carneiro; Risala Shaaban Tekka (International Journal of Dentistry)
Conclusion: The majority of maxillary and mandibular first permanent molars from Tanzanian adult dental patients had an external morphology of three and two separated roots with distal curvature of mesiobuccal roots of maxillary molars being statistically significantly related to age. The internal morphology of maxillary mesiobuccal and mandibular mesial roots showed higher proportion of two canal orifices with mean distance varying between 0.11 and 0.39 mm. Variations in root morphology were not related to sex.